Assessing suboxone access in community pharmacies: Secret shopper model - Bethany A. DiPaula; Catherine E. Cooke (Elsevier, 2023)
Objective: To assess whether Maryland community pharmacies had Suboxone available for dispensing. Methods: This cross-sectional study used a secret shopper model to contact public-facing community pharmacies in Maryland. The secret shopper, guided by a script, asked whether a prescription for Suboxone was available for the same or next day pick-up. A small convenience sample of pharmacies who did not have Suboxone available received an in-person visit to inquire about medication availability and dispensing barriers. Results: After contacting 99% (n = 1046) of Maryland public-facing pharmacies, Suboxone was confirmed available for immediate pick-up in 31% (n = 326). The remaining did not have, would not disclose, or had limited access (existing patients or specific providers only). Significant differences in Suboxone availability were found for National Capital vs. Baltimore metro region and when pharmacist asked questions vs. no questions. Of the 11 pharmacy visits completed, 10 said they had Suboxone currently in stock, with one clarifying medication was for existing patients only. Conclusion: About 69% of patients may face challenges when calling to find out whether they can obtain Suboxone in Maryland pharmacies. Better patient education and more thorough pharmacy-level investigation of system and workflow barriers could offer solutions.